PENTINGNYA WADAH DAN SARANA PEMASARAN PRODUK GUNA PENINGKATAN EKSISTENSI UMKM - Bunyamin; Siti Munfaqiroh; Darti Djuharni; Enggar Nursasi; Tutik Arniati; Istutik; Syerly Hesti Erawati; Muniroh; Tachjuddin; M. Soedarman (P3M Politeknik Negeri Malang, 2022)
The purpose of Community Service activities carried out by STIE Malangkucecwara lecturers is to help MSMEs so that their products are better known by the public. During a pandemic like this, it is very important to help MSMEs in developing and marketing their products. All sectors feel the sluggish economic activity. For this reason, the support of the government and academia is very much needed by MSMEs in maintaining and improving their business. By facilitating SMEs in product exhibitions at the MSME Expo, it is hoped that MSMEs will be even more motivated in improving the quality of their products. With this Expo activity, MSME products in Blimbing Subdistrict, Malang City, which consist of sambal pecel, pastries, jamu turmeric tamarind, brownies, sweet salad spices and dolls have the opportunity to market their products. So that MSME products can be better known to the wider community. In this activity, MSMEs also distribute brochures and business cards to add promotional tools, so that with the end of the Expo, product marketing will continue.